Nearby early-type galactic nuclei at high resolution: Dynamical black hole and nuclear star cluster mass neasurements - Nguyen, D; Seth, A; Neumayer, N; Kamann, S; Voggel, K; Cappellari, M; Picotti, A; Nguyen, P; Böker, T; Debattista, V; Caldwell, N; McDermid, R; et al. (American Astronomical Society, 2018)
We present a detailed study of the nuclear star clusters (NSCs) and massive black holes (BHs) of four of the nearest low-mass early-type galaxies: M32, NGC 205, NGC 5102, and NGC 5206. We measure the dynamical masses of both the BHs and NSCs in these galaxies using Gemini/NIFS or VLT/SINFONI stellar kinematics, Hubble Space Telescope (HST) imaging, and Jeans anisotropic models. We detect massive BHs in M32, NGC 5102, and NGC 5206, while in NGC 205, we find only an upper limit. These BH mass estimates are consistent with previous measurements in M32 and NGC 205, while those in NGC 5102 and NGC 5206 are estimated for the first time and both found to be <106 M⊙. This adds to just a handful of galaxies with dynamically measured sub-million Me central BHs. Combining these BH detections with our recent work on NGC 404ʼs BH, we find that 80% (4/5) of nearby, low-mass (109–1010 M⊙; σ⋆ ~ 20–70 km s−1) early-type galaxies host BHs. Such a high occupation fraction suggests that the BH seeds formed in the early epoch of cosmic assembly likely resulted in abundant seeds, favoring a low-mass seed mechanism of the remnants, most likely from the first generation of massive stars. We find dynamical masses of the NSCs ranging from 2 to 73 × 106 M⊙ and compare these masses to scaling relations for NSCs based primarily on photometric mass estimates. Color gradients suggest that younger stellar populations lie at the centers of the NSCs in three of the four galaxies (NGC 205, NGC 5102, and NGC 5206), while the morphology of two are complex and best fit with multiple morphological components (NGC 5102 and NGC 5206). The NSC kinematics show they are rotating, especially in M32 and NGC 5102 (V⁄σ⋆ ~ 0.7).